Garrett Ranking of Constraints and Satisfaction of Makhana (Euryale ferox) Growers in Bihar - Amrit Warshini; R.K. Doharey; N.R. Meena; Aman Verma; Vishal Yadav; Anurag Dixit (Indian Journal of Extension Education, 2025)
The study aimed to identify the key constraints Makhana (Euryale ferox) growers face in the districts of Madhubani and Darbhanga, Bihar, and assess their satisfaction with various aspects of Makhana cultivation. The study was conducted in 2024 and 2025, the research involved a total of 360 randomly selected Makhana growers (262 male and 98 female). A descriptive research design was employed, utilizing the Garrett Ranking Method to evaluate constraints and a 5-point Likert scale to assess satisfaction levels across various aspects of cultivation, including production, income, labour, and postharvest practices. The findings revealed that the most significant challenges included skilled labour requirements, land ownership issues, and lack of technological support. Farmers expressed moderate satisfaction with cultivation practices, although satisfaction with income generation was notably low. The study highlights the need for improved technology, better market access, and increased financial support to enhance both productivity and the economic sustainability of Makhana farming. Addressing these constraints could improve farmer satisfaction and ensure the long-term viability of Makhana cultivation in the region.